Tradução, adaptação cultural e validação do Frail Non-Disabled Questionnaire para o contexto brasileiro - Lanzotti, Rafaela Brochine (2019)
Frailty syndrome can be conceptualized as a state of age-related physiological vulnerability, produced due the decrease of homeostatic reserve and organism’s reduced capacity for dealing with health issues. The aim of this study was translating, analyzing, and validating Frail Non-Disabled Questionnaire (FiND) for Brazilian context. This is a methodological study which followed the international recommendations for instruments in health field: initial translation, translations’ synthesis, retro translation, revision by a committee of experts, pre-test, and evaluation of scale’s psychometric properties. All the ethical aspects were respected. Translation and retro translation was conducted by two independent and qualified translators. The review carried by the committee of experts revealed the validity of the instrument content. Pre-test phase revealed the FiND to be an instrument whose application and comprehension was easy. The evaluation of scale’s psychometric properties was calculated by the Kuder-Richardson test and Intraclass Correlation Coefficient, which showed satisfactory values. According to these tests, the proposed instrument is reliable and replicable. In addition to that, it was verified the concurrent validity by means of Spearman’s Correlation Coefficient and Receiver Operating Characteristic Curve (ROC curve). Results suggested positive correlation between FiND and Fried’s frailty phenotype, as well as satisfactory values for sensibility, specificity, positive and negative predictive value, and accuracy. The validity of instrument’s construct convergence was analyzed by Spearman’s Correlation Coefficient, which indicated a positive correlation between the FiND and depressive symptoms. The same analysis revealed negative correlations with nutritional and cognitive states, as well as with quality of life’s physical components. Comparison of means was used to analyze discriminant validity between robust, non-frail, and frail groups considering the following: with or without depressive symptoms; better or worse perception on quality of life; and adequate nutritional state, at risk for malnutrition, or in a malnutrition state. All these comparisons were statistically significant. Considering the proposed goals, as well as the obtained results, it is concluded that FiND was translated, adapted, and validated for Brazilian context, which allows its use for future research on incapacity and frailty in community-dwelling older adults; it also instrumentalizes health professionals, caregivers, and family members who works in places that attend the elderly.